Impact of Engineered Expression of Mitochondrial Association Factor 1b on Toxoplasma gondii Infection and the Host Response in a Mouse Model - Elizabeth D. English (American Society for Microbiology, 2018)
ABSTRACT The opportunistic intracellular parasite Toxoplasma gondii causes a lifelong chronic infection capable of reactivating in immunocompromised individuals, which can lead to life-threatening complications. Following invasion of the host cell, host mitochondria associate with the parasitophorous vacuole membrane. This phenotype is T. gondii strain specific and is mediated by expression of a host mitochondrial association-competent (HMA+) paralog of the parasite protein mitochondrial association factor 1 (MAF1b). Previous work demonstrated that expression of MAF1b in strains that do not normally associate with host mitochondria increases their fitness during acute infection in vivo. However, the impact of MAF1b expression during chronic T. gondii infection is unclear. In this study, we assess the impact of MAF1b expression on cyst formation and cytokine production in mice. Despite generally low numbers of cysts generated by the in vitro culture-adapted strains used in this study, we find that parasites expressing MAF1b have higher numbers of cysts in the brains of chronically infected mice and that MAF1b+ cyst burden significantly increases during the course of chronic infection. Consistent with this, mice infected with MAF1b+ parasites have higher levels of the serum cytokines RANTES and VEGF (vascular endothelial growth factor) at day 57 postinfection, although this could be due to higher parasite burden at this time point rather than direct manipulation of these cytokines by MAF1b. Overall these data indicate that MAF1b expression may also be important in determining infection outcome during the chronic phase, either by directly altering the cytokine/signaling environment or by increasing proliferation during the acute and/or chronic phase. IMPORTANCE The parasite Toxoplasma gondii currently infects approximately one-third of the world’s population and causes life-threatening toxoplasmosis in individuals with undeveloped or weakened immune systems. Current treatments are unable to cure T. gondii infection, leaving infected individuals with slow-growing tissue cysts for the remainder of their lives. Previous work has shown that expression of the parasite protein mitochondrial association factor 1 (MAF1b) is responsible for the association of T. gondii parasites with host mitochondria and provides a selective advantage during acute infection. Here we examine the impact of MAF1b expression during chronic T. gondii infection. We find that mice infected with MAF1b-expressing parasites have higher cyst burden and cytokine levels than their wild-type counterparts. A better understanding of the genes involved in establishing and maintaining chronic infection will aid in discovering effective therapeutics for chronically infected individuals.